Analisis Peran Pelatihan Kerja Oleh Unit Pelaksana Teknis Daerah Latihan Kerja Provinsi NTT Terhadap Peningkatan Produktivitas Peserta Pasca Pelatihan - Julius Innosensius Beon; Marselina Ratu; Novi Theresia Kiak (Journal of Islamic Economics and Finance, 2024)
qualified labor is an important factor in achieving economic development of a region. To improve the quality of the workforce, job training is needed that can provide job skills for the workforce. This study aims to explain the benefits of job training for improving the quality of the workforce based on the policies and programs of the NTT Provincial work training UPTD and explain the productivity of graduate participants after attending job training. This study uses a descriptive qualitative approach, by conducting structured interviews to informants and instructors UPTD work training, and also graduates from job training. The results showed that job training is very beneficial for improving the quality of the workforce through the empowerment of Labor expertise in order to have skills, attitudes, and knowledge about the world of work. Many of the job training graduates have been successful in their efforts and are able to absorb other workers, but not infrequently job training graduates who fail to achieve productivity due to not being serious when attending job training, lack of availability of business capital, and lack of readiness to compete in the world of work. In order for job training graduates to achieve their productivity, supervision is needed by the Uptd of work training and also financial assistance from local governments for the effectiveness of training activities and the provision of business capital to support the efforts of job training graduates.